Induction of tumor necrosis factor alpha by spherules of Coccidioides immitis. - Slagle, D C (1989)
The cytokine tumor necrosis factor alpha (TNF-alpha) functions as an immunomodulatory protein and as a mediator of cachexia. We report that viable or Formalin-killed spherules of Coccidioides immitis induced the secretion of TNF-alpha by peritoneal-exudate cells from BALB/c mice. The identification of the cytokine as TNF-alpha was based on its lytic activity against the TNF-alpha-sensitive LS murine fibrosarcoma cell line but not the TNF-alpha-resistant LR cell line, its neutralization by rabbit anti-TNF-alpha, and its secretion by peritoneal cells having characteristics of macrophages. The induction of TNF-alpha was to spherules and not to contaminating lipopolysaccharide (endotoxin), as evidenced by the finding that polymyxin B, a reagent that blocks the TNF-alpha-inducing component of lipopolysaccharide, did not negate the production of TNF-alpha in response to spherules, whereas pretreatment of spherules with hyperimmune goat antiserum to spherulin neutralized the induction of TNF-alpha by these cells. The demonstration that C. immitis activates macrophages to secrete TNF-alpha in vitro is a new finding and warrants studies to determine whether this cytokine is produced during active coccidioidomycosis.